Ensuring Quality Assurance in Indonesian Higher Education: Challenges and Strategies - Jarodi, Odi; Pramono, Suwito Eko; Khafid, Muhammad; Yulianto, Arief (Universitas Negeri Semarang, 2024)
This article examines the challenges and strategies of quality assurance in Indonesian higher education through a comprehensive library research approach. Quality assurance is essential for raising educational standards and ensuring continuous improvement. The methodology involves systematically collecting and analyzing existing literature, including books, peer-reviewed journal articles, government reports, and policy documents, to extract key themes and findings related to quality assurance practices. The study highlights significant challenges, such as policy inconsistency, inadequate institutional support, and the need for a cultural shift towards quality. Additionally, the integration of technology and transition to student-centered learning present further complications. Despite these obstacles, ongoing initiatives aim to foster a culture of continuous improvement and alignment with global standards. The article concludes that effective quality assurance requires a multifaceted approach involving organizational readiness, stakeholder engagement, and a commitment to continuous improvement. By addressing these challenges and leveraging best practices, Indonesian higher education institutions can enhance their quality assurance systems, ultimately contributing to the development of competitive graduates and societal progress.